Analysis of Total Plate Count Microba in Fresh (Rastrelliger sp.) Mackerel fish` of Sorong City West Papua - Sukmawati Sukmawati; Iksan Badaruddin; Evi Selfiana Simohon (Samakia : Jurnal Ilmu Perikanan, 2020)
Fish is one of the fishery food ingredients that are needed by humans, because in the fish meat there are compounds needed by the body. Such as the content of protein compounds, fats, carbohydrates, vitamins and mineral salts. Sorong in the city of mackerel is one of the fish that are of interest to the community, and its availability is abundant at the fish auction place in the city of Sorong. But in general the consumption of mackerel has not been tested either chemically or microbiologically based on the background of the purpose of this study is to determine the total microbial plate count in fresh mackerel (Rastelliger sp.) In Sorong City, West Papua. The method in this research was descriptive method, which is drawing the number of microbes through the test of the total number of microbial plates (ALT). Based on the results of the study which stated the average of the five samples approved were in sample A and sample B the amount of ALT was 3.7 x 104 cFU/mL, sample C and sample D were 1.02 x 105 cFU/mL, and sample E as much as 2.7 x 105 cFU/mL. The total number of microbial total plates (ALT) or the number of microbial total plates (TPC) in fresh mackerel (Rastrelliger sp.) in the Sorong TPI city does not exceed the maximum Indonesian national standard (SNI), and it is concluded that the fish can be consumed.